2018
DOI: 10.1002/mds.27439
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and risk for Parkinson's disease: A nationwide cohort study

Abstract: Background: Stress has been suggested as a contributing factor in the etiology of Parkinson's Disease (PD), but epidemiological evidence is sparse. Objective: The objective of this study was to explore the association between occupational stress according to the job demands‐control model and the risk for PD. Methods: We conducted a population‐based cohort study with 2,544,748 Swedes born 1920 to 1950 who had an occupation reported in the population and housing censuses in 1980 or, if missing, in 1970. Job dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Women have lower levels of education than men, which may explain the difference. A recent study on the relationship between occupational stress and PD risk shows that high job requirements seem to increase the risk of PD in men, especially among highly educated men [ 33 ], which may partly explain men’s susceptibility to PD.…”
Section: Discussionmentioning
confidence: 99%
“…Women have lower levels of education than men, which may explain the difference. A recent study on the relationship between occupational stress and PD risk shows that high job requirements seem to increase the risk of PD in men, especially among highly educated men [ 33 ], which may partly explain men’s susceptibility to PD.…”
Section: Discussionmentioning
confidence: 99%
“…This model consists of two dimensions: the "demand component" measuring time pressure and psychological/cognitive demands and the "control component" including decision making authority and skill discretion abilities. A recent study on the association between occupational stress according to this model and the risk for PD showed that high job demands appear to increase PD risk in men, especially in men with high education, whereas high job control increases PD risk more strongly in low educated women [57].…”
Section: Environmental Risk Factorsmentioning
confidence: 98%
“…factor (Graziano et al, 2013;Hirsch et al, 2018). Still, the concept of physiological corticostriatal stress remains hypothetical, and the possibility that daily life activities-e.g., jobs with high complexity and demands (Valdé s et al, 2014;Sieurin et al, 2018)-may influence the incidence of PD by increasing habitual behaviors and overloading corticostriatal circuits will require further investigation. Cortical Pathogenic-Pathophysiological Interaction Whether at cortical level pathogenic alterations precede or follow pathophysiological alterations in PD might be a classical chicken-or-egg problem.…”
Section: Cortically Driven Onset and Progression Of Parkinson's Diseamentioning
confidence: 99%